If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + 3y = 7 Solving 3xy + 3y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 3xy + 3y + -3y = 7 + -3y Combine like terms: 3y + -3y = 0 3xy + 0 = 7 + -3y 3xy = 7 + -3y Divide each side by '3y'. x = 2.333333333y-1 + -1 Simplifying x = 2.333333333y-1 + -1 Reorder the terms: x = -1 + 2.333333333y-1
| 0.2x+2.7x=7.7-1.5+2.7x | | 20+x^2+9x=0 | | 2u^2-5u-16=u^2+4 | | f(x)=6x^4+23x^3+19x^2-8x-4 | | 192=1/212b | | 9+8x=23+x | | 2(3-5x)=3(3x+4) | | x-17+x=126 | | X^2+4x+22=-5x+2 | | 5(-4x+3)=10x-2 | | x+4.8=-6.7 | | 8x^3+4x^2+7x-1=0 | | 20(x)+7.5(x)=300 | | 87+95=j | | -35+x^2+-2x=0 | | 36x^4-36x^3+24x^2+9x+6=0 | | n^2+n-20= | | 2600000=.0000113x^3-.000922x^2+.0538x | | 4x-7+2x=2(3x-3) | | -8-3q=25 | | X^2-2x-29=6 | | -3(7x-2)+8x= | | 0.6%*x=7.5 | | 5x^2+2x=8 | | 10y=x^3 | | 8+x^2+-6x=0 | | s^3-st^2+s^2t-t^3= | | 2(j-4)=7(5-3j)+9j | | 48q-33=55q-89 | | 10+7x-7x=2+x | | 12=3+5tanx | | 744584946825981m=4865468136 |